Editorial - Oniwide, Oyetola (NIU Journal of Educational Research, 2025)
This edition of NIU Journal of Educational Research touches on Assessment Practices of Teachers, Digitalized Learning Delivery, The Role of Education in Transforming Youth Identity and Purpose, Leadership Succession Planning in Higher Education and Educational Psychology. One of the papers, in this issue, examines how integrating YouTube technology has an impact on secondary school students’ academic performance and attitudes in Civic Education in Akoko Metropolis, Ondo State, Nigeria, and underscores the need for improving teacher training in digital pedagogy, providing infrastructure for internet access in schools, and reforming curricula to include digital content delivery methods formally. Another paper also reveals persistent challenges Nigeria’s Higher Education, including the absence of formalized succession frameworks, limited leadership development opportunities, resource constraints, and inadequate administrative commitment. Emerging practices emphasize embedding leadership development into academic career pathways, fostering diversity and inclusion in leadership pipelines, and utilizing data-driven technologies for talent management and informed decision-making. The paper therefore, recommends that strengthened policy support, capacity building, and continuous mentorship will be vital to embedding leadership succession into the strategic culture of higher education institutions. On the whole, this edition of NIU Journal of Educational Research features many empirical and theoretical based articles which can be of great benefit to every reader.